A STUDY ON CONSUMER PERCEPTION TOWARDS FAST FOOD RETAIL OUTLETS WITH REFERENCE TO BENGALURU KARNATAKA (Journal of Pharmaceutical Negative Results, 2023)
The Indian economy was a traditional economy with majority of people having a preference towards home cooked food which consist of nutritional value. This was a major challenge to global fast food to setup their business in India. In the present scenario, traditional food is replaced by fast foods. Due to the changes in lifestyle pattern demand for fast food is increasing day by day. Today fast food industry is one of the leading industries in India. This present study is focused on determine youth’s consumption pattern towards fast foods particularly with respect to the frequency of visits and choice of fast food outlets. It is found that most of the customers are willing to spend more if food quality & Improvement in the menu. Major concern is on Employee friendliness, where the food courts can further extend seating space and can bring more marketing strategies to attract more customers.